Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.179
|View full text |Cite
|
Sign up to set email alerts
|

An FPT Algorithm Beating 2-Approximation for k-Cut

Abstract: In the k-Cut problem, we are given an edge-weighted graph G and an integer k, and have to remove a set of edges with minimum total weight so that G has at least k connected components. Prior work on this problem gives, for all h ∈ [2, k], a (2 − h/k)-approximation algorithm for k-cut that runs in time n O(h) . Hence to get a (2−ε)-approximation algorithm for some absolute constant ε, the best runtime using prior techniques is n O(kε) . Moreover, it was recently shown that getting a (2−ε)-approximation for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…To circumvent this, Saran and Vazirani [32] devised two simple polynomial time (2 − 2/k)-approximation algorithms for the problem. In the ensuing years, different approximation algorithms [33][34][35][36][37] have been proposed for the problem, none of which are able achieve an approximation ratio of (2 − ε) for some ε > 0 in polynomial time. In fact, Saran and Vazirani themselves conjectured that (2 − ε)-approximation is intractible for the problem [32].…”
Section: Minimum K-cutmentioning
confidence: 99%
“…To circumvent this, Saran and Vazirani [32] devised two simple polynomial time (2 − 2/k)-approximation algorithms for the problem. In the ensuing years, different approximation algorithms [33][34][35][36][37] have been proposed for the problem, none of which are able achieve an approximation ratio of (2 − ε) for some ε > 0 in polynomial time. In fact, Saran and Vazirani themselves conjectured that (2 − ε)-approximation is intractible for the problem [32].…”
Section: Minimum K-cutmentioning
confidence: 99%
“…Our approximate DP technique turns out to be useful to get a 1.81-approximation for k-Cut in FPT time, improving on our previous approximation of ≈ 1.9997 [GLL18]. In particular, the laminar cut problem from [GLL18] also has a tight T-tree structure, and hence we can use (a special case of) our approximate DP algorithm to get a (1 + ε)-approximation for laminar cut, instead of the 2 − ε-factor previously known. Combining with other ideas in the previous paper, this gives us the 1.81-approximation.…”
Section: Introductionmentioning
confidence: 58%
“…, S k be the components maintained by the algorithm. In [GLL18], a is defined to be the smallest value of k when both the weight of the min-cut, as well as one-third of the weight of the min-4-cut, becomes bigger than w(∂S * 1 )(1 − ε 1 /3), for some ε 1 > 0. Moreover, b ∈ [k] is the smallest number such that w(∂S * b ) > w(∂S * 1 )(1 + ε 1 /3).…”
Section: B An 181-fpt Approximation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, to the best of our knowledge, prior to this work, there was no approximation algorithm with a ratio better than 2 for any major class of graphs. It is also worth mentioning that a recent work by Gupta et al [19] showed that using an FPT algorithm the approximation factor of 2 can be beaten in the k-cut problem. They showed that there exists a 2 − ǫ approximation algorithm that runs in time 2 O(k 6 )Õ (n 4 ).…”
Section: Introductionmentioning
confidence: 99%